Діалог як форма етичного спілкування: фольклорний фестиваль, якого не було - Хазан-Рокем, Г. (Народна творчість та етнографія, 2008)
The article addresses the issue of dialogical emergence of culture focusing on a tripartite research enterprise involving Palestinian, Israeli and US scholars. The research described was a project of applied research, i.e. in preparation of a representation of Jerusalem at the American Folklife Festival in Washington D.C. The topics discussed include the political context of folklore, public folklore and the ethical aspects of research. Finally the representation of a particular Jewish festival, Sukkoth, is analyzed in parallel to the analysis of the Folklife Festival, highlighting some theoretical aspects.